Inspired by Daniel Liu

Geometry Level 5

f ( x ) = 8 x 3 12 x 2 + b x + d \Large f\left( x \right) ={ 8x }^{ 3 }-{ 12x }^{ 2 }+bx+d

For variables b b and d d independent of x x , we are given the function f ( x ) f(x) as described above to have roots 1 α , β , γ 1 -1\le\alpha ,\beta ,\gamma \le 1 and that

α + β + γ = 1 + 4 sin cos 1 ( α ) 2 × sin cos 1 ( β ) 2 × sin cos 1 ( γ ) 2 \alpha +\beta +\gamma =1+4\sin { \frac { \cos ^{ -1 }{ (\alpha ) } }{ 2 } } \times \sin { \frac { \cos ^{ -1 }{ (\beta) } }{ 2 } } \times \sin { \frac { \cos ^{ -1 }{ (\gamma ) } }{ 2 } }

Evaluate b + d b+d .

This problem is original.


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let's start with the Vieta's formula

We then know that α + β + γ = 3 2 \displaystyle \alpha + \beta + \gamma = \frac{3}{2}

sin ( cos 1 ( α ) 2 ) = 1 cos ( cos 1 ( α ) ) 2 \displaystyle \sin(\frac{\cos^{-1}(\alpha)}{2})=\sqrt{\frac{1-\cos(\cos^{-1}(\alpha))}{2}} and is the same for the rest.

then the equation becomes

3 2 = 1 + 4 2 2 × ( 1 α ) ( 1 β ) ( 1 γ ) \displaystyle \frac{3}{2} = 1+\frac{4}{2\sqrt{2}} \times \sqrt{(1-\alpha)(1-\beta)(1-\gamma)}

1 8 = ( 1 α ) ( 1 β ) ( 1 γ ) = 1 ( α + β + γ ) + ( α β + α γ + β γ ) + α β γ \displaystyle \frac{1}{8}= (1-\alpha)(1-\beta)(1-\gamma)=1-(\alpha + \beta + \gamma)+(\alpha \beta +\alpha \gamma + \beta \gamma) + \alpha \beta \gamma = 1 3 2 + b + d 8 \displaystyle =1-\frac{3}{2}+\frac{b+d}{8}

5 8 = b + d 8 \displaystyle \frac{5}{8}=\frac{b+d}{8}

so b + d = 5 \displaystyle b+d= \boxed{5}

Shivamani Patil
Jul 5, 2015

Here we can substitute cos a = α , cos b = β , cos c = γ \cos { a } =\alpha ,\cos { b } =\beta ,\cos { c } =\gamma \quad as 1 α , β , γ 1 -1\le \alpha ,\beta ,\gamma \le 1 .

α + β + γ = 1 + 4 sin a 2 × sin b 2 × sin c 2 = cos a + cos b + cos c \therefore \alpha +\beta +\gamma =1+4\sin { \frac { a }{ 2 } } \times \sin { \frac { b }{ 2 } } \times \sin { \frac { c }{ 2 } } =\cos { a } +\cos { b } +\cos { c } \quad --Result 1 1

Now one observation.Observe that Result 1 1 is conditional trigonometrical identity which holds when a + b + c = 180 ° a+b+c=180° .

By Veita we have α + β + γ = 3 2 = cos a + cos b + cos c \alpha +\beta +\gamma =\frac { 3 }{ 2 }=\cos { a } +\cos { b } +\cos { c } .

a = b = c = 60 ° \therefore a=b=c=60° (Why?Proof left for reader!)

cos a = cos b = cos c = 1 2 = α = β = γ \therefore \cos { a } =\cos { b } =\cos { c } =\frac { 1 }{ 2 } =\alpha =\beta =\gamma .

Again by Veita we have α β + γ α + β γ = b 8 = 3 4 \alpha \beta +\gamma \alpha +\beta \gamma =\frac { b }{ 8 } =\frac { 3 }{ 4 } and α β γ = d 8 = 1 8 \alpha \beta \gamma =\frac { -d }{ 8 } =\frac { 1 }{ 8 } .

Giving b = 6 b=6 and d = 1 d=-1 .

b + d = 5 \boxed{b+d=5} .

Finishing the solution off (I'm the reader!):

WLOG b , c π 2 b, c\le\dfrac{\pi}{2} . By Jensen Inequality, cos a + cos b + cos c cos a + 2 cos ( b + c 2 ) = cos a + 2 sin ( a 2 ) \cos a + \cos b + \cos c\le \cos a + 2\cos\left(\dfrac{b+c}{2}\right) =\cos a + 2\sin\left(\dfrac{a}{2}\right) Letting x = sin ( a 2 ) x=\sin\left(\dfrac{a}{2}\right) we get cos a + 2 sin ( a 2 ) = 1 2 x 2 + 2 x 3 2 \cos a + 2\sin\left(\dfrac{a}{2}\right) =1-2x^2+2x\le \dfrac{3}{2} with equality case x = sin ( a 2 ) = 1 2 a = π 3 b = c = π 3 x=\sin\left(\dfrac{a}{2}\right)= \dfrac{1}{2}\implies a=\dfrac{\pi}{3}\implies b=c=\dfrac{\pi}{3} .

Daniel Liu - 5 years, 11 months ago

Log in to reply

Ya good that you finished off.

shivamani patil - 5 years, 11 months ago

Log in to reply

Wait I see an error, let me fix it.

EDIT: done fixing. It should be right now.

Daniel Liu - 5 years, 11 months ago

Log in to reply

@Daniel Liu Ya it seems good now:)

shivamani patil - 5 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...